(untitled) (Biological Sciences - PJSIR, 2002)
The extracts of neem seed kernels and leaves and their powders were tested for the repellent and antifeedant activities against Tribolium castaneum (Herbst) and Rhizopertha dominica (Fabricius) respectively. The best repellent activity class (iv) was observed in fresh seed kernels extracted in ethyl alcohol at 150 mg cm2 . Whereas the benzene, hexane and acetone extracts of the seed kernels were not effective at the same dose. Dry powder of fresh seed kernels protected wheat from infestation upto one year at higher dose.